AP2017 : 12th International Conference of Archaeological Prospection, 12th-16th september 2017, University of Bradford - Jennings, Benjamin,; Gaffney, Christopher,; Sparrow, Thomas,; Gaffney, Sue, (Archaeopress Publishing Ltd, 2017)
This volume is a product of the International Conference of Archaeological Prospection 2017 which was hosted by the School of Archaeological and Forensic Sciences at the University of Bradford. This event marked a return to the location of the inaugural conference of archaeological prospection which was held in Bradford in 1995. The conference is held every two years under the banner of the International Society for Archaeological Prospection. The Proceedings of 12th International Conference of Archaeological Prospection draws together over 100 papers addressing archaeological prospection techniques, methodologies and case studies from around the world.